Long-term Results of Two Different Surgical Techniques Used in Carpal Tunnel Syndrome - Ercan, Serdar; Ataizi, Zeki Serdar (Indian Journal of Neurosurgery, 2021)
Objective Carpal tunnel syndrome (CTS), the compression of the median nerve under the carpal ligament, is the most common peripheral nerve entrapment of the upper extremity. While conservative treatment is used for patients with mild and moderate symptoms, surgical treatment is preferred for severe symptoms. The aim of the study is to evaluate the difference between transverse and longitudinal incision by comparing postoperative pain and recurrence rates.Methods The patients were divided into two groups according to the surgical incision type. Surgical intervention was applied to patients in group T (transverse incision) and group L (longitudinal incision) by the same two surgeons in each group. All patients were followed-up with electromyography (EMG) and performance scale before and after surgical treatment. If the postoperative EMG result was similar to the preoperative EMG result, it was accepted as recurrent CTS.Results A total of 418 patients were included to the study. Six patients in the group T with transverse incision, and 18 patients in the group L with longitudinal incision, were reoperated for an average of 6 ± 2 months after the primary surgery.Conclusion Complications are less, and recurrent nerve compression is less in longitudinal approach, since surgical intervention is performed by seeing the median nerve directly.
Keywords: peripheral nerve; carpal tunnel; entrapment; surgical approach; recurrence